Resistance of Traditional Traderson Market Relocation Policy in Aksara Market, Medan, Indonesia - Nasution, Marsolina; Siahaan, Asima Yanti; Achmad, Nurman; Ismail, Rizabuana; Sitorus, Henry (Budapest International Research and Critics University, 2021)
This study aims to explain the form of resistance from traditional traders after the fire against the relocation policy established by the Medan City Government, Indonesia. In-depth interviews were conducted with 6 informants who are traditional traders at Aksara Market and 1 informant as a representative from the Medan city government. This data was collected to find out the opinion and perspective of the community towards the relocation policy and reasons for the Medan city government to relocate Aksara traders to other places. The results indicate that traders in the Aksara market disagree with the relocation policy determined by the Medan City Government. Therefore, people represented their resistance by selling along the sidewalks of the Aksara market which had burned and caused traffic jams. Moreover, they established a group of fire victim traders called PK2PTAM (Representative of Fire Victims Traditional Traders of Aksara Market Medan) to struggle with the revitalization of Aksara Market. The main reason for the Medan City government in issuing this relocation policy was the flyover construction project which affects the location of Aksara market.Â